Radical cystoprostatectomy and ileal neobladder substitution: an experience with a T2 invasive bladder tumor patient (Annals of Medical Research, 2021)
None
Keywords: s : Invasive bladder canser, surgery, radical cystoprostatectomy, ileal bladder, diversions